Migration in Irish History 1607-2007 - Fitzgerald, Patrick. author. aut Link
XX, 403 p.
Keywords: Migration - people moving in as immigrants, around as migrants, and out as emigrants - is a major theme of Irish history. This is the first book to offer both a survey of the last four centuries and an integrated analysis of migration, reflecting a more inclusive definition of the 'people of Ireland'.